2005
DOI: 10.2214/ajr.184.1.01840035
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Confluence of Lymph Trunks: Detectability and Morphology on Heavily T2-Weighted Images

Abstract: Abdominal confluence of lymphatics seems to be present on most of the heavily T2-weighted images. Its morphologic details and extensions can be visualized on images reconstructed with a maximum-intensity-projection algorithm. Any disorder does not necessarily lead to dilatation of these lymphatic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…Few previous studies have reported the imaging appearance of CC [15,16]; the frequency of seeing the CC on lymphangiography ranged from 30% to 53% [4], but only 1.7% on CT [17] On MRI, Erden et al [18] detected CC in 96% of patients on heavily T2-weighted images. Unlike these investigators, we used a threshold diameter of 2 mm for identifying CC because of potential variability in identifying structures smaller than a pixel.…”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies have reported the imaging appearance of CC [15,16]; the frequency of seeing the CC on lymphangiography ranged from 30% to 53% [4], but only 1.7% on CT [17] On MRI, Erden et al [18] detected CC in 96% of patients on heavily T2-weighted images. Unlike these investigators, we used a threshold diameter of 2 mm for identifying CC because of potential variability in identifying structures smaller than a pixel.…”
Section: Discussionmentioning
confidence: 99%
“…For example, considering that the classical location of the CC (according to anatomical and surgical texts) occurs at L1-L2, a more superior location has a greater potential to be misdiagnosed as a pathologic lesion of the posterior mediastinum. Several radiological studies demonstrating the recent advancement of imaging techniques have proved the importance of accurate anatomical knowledge of the TD and CC (Erden et al, 2005). For instance, the radiographic appearance of mediastinal nodes has been associated with TD anatomic variations (Cha and Sirijintakarn, 1976), and the CC has been shown to mimic the appearance of an enlarged retrocrural lymph node (Gollub and Castellino, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…As a conclusion, anatomic variations of the thoracic duct are numerous and must be considered to avoid complications when doing surgery. nance imaging [2,11]. These methods are not useful in practice.…”
Section: Omer Akcali Amac Kiray Ipek Ergur Suleyman Tetik Emin Alicimentioning
confidence: 99%